2018
DOI: 10.1002/jat.3744
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract may induce lysosomal storage disease‐like adverse health effects

Abstract: Cigarette smoke is known to be associated with the incidence of a variety of pulmonary diseases, and alveolar macrophages are a key player in the defense mechanism against inhalable toxicants. Herein, we have found that a hydrophilic fraction in smoke extracts from 3R4F reference cigarettes (CSE) contains high concentrations of volatile substances compared to cigarette smoke condensate (amphoteric fraction). We also identified the toxic mechanism of CSE using MH‐S, a mouse alveolar macrophage cell line. CSE de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Although it has been well-recognized that cigarette smoke is the most common cause of COPD, the specific mechanisms responsible have not yet been elucidated. 16 , 17 This study analyzed the last 15 years of datasets (until August 2020) available from the GEO database, and found that there was an extensive and significant degree of gene differential expression of AM between the COPD smoking and non-COPD smoking group. It was found that people with COPD have a number of significantly differently expressed genes related to energy metabolism or oxidative stress than those without COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been well-recognized that cigarette smoke is the most common cause of COPD, the specific mechanisms responsible have not yet been elucidated. 16 , 17 This study analyzed the last 15 years of datasets (until August 2020) available from the GEO database, and found that there was an extensive and significant degree of gene differential expression of AM between the COPD smoking and non-COPD smoking group. It was found that people with COPD have a number of significantly differently expressed genes related to energy metabolism or oxidative stress than those without COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled tobacco smoke comprises substances such as carbon monoxide (CO), formaldehyde, acetaldehyde, benzopyrenes, and nicotine which can enter the circulation 3 , 4 . Most of these substances are toxic and can cause tissue damage by inducing oxidative stress and inflammation 5 7 . In addition, CO binds to hemoglobin to form carboxyhemoglobin which reduces oxygen-carrying capacity and oxygen utilization 8 .…”
Section: Introductionmentioning
confidence: 99%
“…2 CS contains more than 4000 chemicals, many of which have been associated with deleterious health consequences. 3 Particularly, oxidants, such as nicotine, acrolein, and carbon monoxide, can be detrimental. 4 Oxidative damage resulting from oxidants of CS, such as nitric oxide and carbonyls, plays major roles in the development of many tobacco-caused diseases including respiratory and heart diseases, cancers, and others.…”
mentioning
confidence: 99%